(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2024)
The increasing cases of land fraud in land administration is a very worrying trend as it erode public confidence in land administration. The main objective of this paper is to identify the loopholes in the statutes applied in the land registration process such as the National Land Code (Act 828), the Contract Act 1950 (Act 136), the Power of Attorney Act 1949 (Act 424) and the Statutory Declaration Act 1960 ( Act 783). As well as provide proposed suggestions for harmonising these statues in order to make improvements and reduce the number of fraud cases in the area of land dealings. This discussion also examines several statutes, whether they are able to provide solution to the problem of land fraud. Therefore, it is important that these statutes be immediately amended in order to protect landowners and interested parties who have become victims due to the existing provisions, which may not offer remedies, protection or a limited scope that denies protection of fraud victims. The library research and content analysis methods are being used in this study such as decided cases, books, articles and journals. The findings of this research indicates that there are gaps in these statutes that allow for land fraud to be exercised. This study will outline several recommendations for improvement to ensure the interests and rights of all parties involved are protected. Keywords: Loopholes, selected statutes, land fraud, land administration, indefeasibility of title, Torrens system Full text: PDF